Maternity leave and reduced future earning capacity - Baker, D (My University, 2011)
In 2011 the Paid Parental Leave Act 2010 was enacted in Australia. This new scheme provides 18 weeks of paid leave at the minimum wage to most Australian workers who, since the beginning of 2011 have had a child. The public funding of this leave addresses the previous disparity that saw only four out of ten women of child-bearing age having access to paid maternity leave. While welcome, this payment will not address the longer term wage penalty experienced by women who take leave around childbirth. An analysis of the Household, Income and Labour Dynamics in Australia (HILDA) survey found that among new mothers returning to work within 12 months of taking leave, their wage growth was lower in the first three years, compared with the average wage rise received by women reported in the ABS Labour Price Index. A method for measuring this phenomenon in the future should be a part of the government's 2013 review of the Paid Parental Leave scheme.
Family Matters
Keywords: Income & Finance -- Income inequality; Employment -- Parental leave; Income, wealth and finances; Labour market; Employment; Income & Finance; Income inequality; Parental leave; Income, wealth and finances; Employment and unemployment